اثر الرواية الجديدة في رواية 2084" حكاية العربي الاخير " لواسيني الأعرج - علاء الدين, عبدي (كلية الأدب العربي والفنون, 2024)
تهدف هذه الدراسة إلى كشف أثر الرواية الجديدة وفنياتها الغربية في رواية "2084 " حكاية العربي الأخير للجزائري واسيني الأعرج، وذلك برصد تجليات التقنيات الروائية الغربية الجديدة من عتبات وأزمنة وأمكنة وشخصيات في الرواية الجزائرية من خلال أنموذج روائي جزائري متكامل متمثل في رواية 2084 حكاية العربي الأخير. يستند هذا البحث على منهج وصفي تحليلي مدعم بآليات الدراسة المقارنة. وقد جاءت هذه المذكرة في مدخل وفصلين إذ تناولت في المدخل الرواية الجديدة المفهوم، النشأة والتطور، كما درست في الفصل الأول أثر الرواية الجديدة في الرواية الجزائرية بصفة عامة، وبينت في الفصل الثاني بشكل تطبيقي محض أثر الرواية الجديدة في رواية "2084 حكاية العربي الأخير" للأعرج واسيني. وفي الختام نرجو أن يسهم هذا البحث في تبيان أثر الرواية الغربية الجديدة في رواية "2084 حكاية العربي الأخير" وتوضيح تجليات هذا الأثر في الرواية الجزائرية بصفة عامة. This study aims to reveal the impact of the new novel and its Western techniques on the Algerian novel "2084: The Last Arab Story" by Wassini Al-Araj. It investigates the manifestations of new Western narrative techniques, such as thresholds, times, places, and characters, in the Algerian novel through a comprehensive Algerian narrative model exemplified by the novel "2084: The Last Arab Story." This research is based on a descriptive-analytical method supported by comparative study tools. The dissertation is divided into an introduction and two chapters. The introduction addresses the concept, origin, and development of the new novel. The first chapter explores the impact of the new novel on Algerian literature in general. The second chapter specifically applies this examination to "2084: The Last Arab Story" by Wassini Al-Araj. In conclusion, we hope this research will contribute to clarifying the influence of the new Western novel on "2084: The Last Arab Story" and elucidate the manifestations of this influence on Algerian literature in general.
Keywords: الرواية الجديدة، حكاية العربي الأخير 2084، واسيني الأعرج، جورج أرويل 1948; new novel, 2084 The Last Arab Story, Wassini Al-Araj, George Orwell, 1984